Peran Komunikasi terhadap Tujuan Khotbah yang Komunikatif dan Relevansinya bagi Pelayanan Hamba Tuhan Masa Kini - Hardi Josetyowanto (Jurnal Salvation, 2021)
Abstract: This paper discusses how the role of communication through khotah can be implemented by god's servants in ecclesiastical ministry. The method that researchers use in deciphering this topic is qualitative research methods with a Library study approach. The description on this topic states that oral communication plays an important role in the ministry of preaching. Preachers who are adept at communicating are certainly more likely to get the expected results. Good oral communication characterizes clear, engaging, beautiful (or fun), informative, reassuring, thought-provoking, heartwarming, meeting the listener's needs. Communicating the message of God's word would certainly consider communicant. In the process of communicating the receiver will show a diverse response in the science of communication, the process is called encoding. Preaching means explaining God's word communicatively so that the words delivered thousands of years ago become alive and relevant in the ins and outs of the listener's life. Therefore achieving the goal of communicative preaching in the congregation must pay attention to the elements of communication. These elements must be able to synergize, such as the role of the message, the role of the communicator, the role of the communicant, the role of how to convey, the role of results, and the role of feedback.   Abstrak: Tulisan ini mengulas bagaimana peran komunikasi melalui khotah dapat diimplementasikan oleh hamba Tuhan dalam pelayanan gerejawi. Metode yang peneliti gunakan dalam menguraikan topik ini adalah metode penelitian kualitatif dengan pendekatan kajian Pustaka. Uraian pada topik ini menyatakan bahwa komunikasi lisan memainkan peran penting dalam pelayanan berkhotbah. Pengkhotbah yang mahir dalam berkomunikasi sudah tentu lebih mungkin mendapat hasil yang diharapkan. Komunikasi lisan yang baik mencirikan jelas, menarik, indah (atau menyenangkan), informatif, meyakinkan, merangsang pikiran, mengharukan, memenuhi kebutuhan pendengar. Mengkomunikasikan pesan firman Tuhan tentunya akan mempertimbangkan komunikan. Dalam proses berkomunikasi penerima akan menunjukkan respons yang ragam dalam ilmu komunikasi, proses itu disebut encoding. Berkhotbah berarti menjelaskan firman Allah secara komunikatif sehingga firman yang disampaikan ribuan tahun yang lalu itu menjadi hidup dan relevan dalam seluk beluk kehidupan pendengar. Oleh sebab itu mencapai tujuan khotbah yang komunikatif dalam jemaat harus memperhatikan unsur-unsur komunikasi. Unsur-unsur ini harus dapat bersinergi, seperti pada peran pesan, peran komunikator, peran komunikan, peran cara menyampaikan, peran hasil, dan peran feedback.